Analysis of the Application of Sanctions and Ta'widh in the Murabahah Financing System at the BMT Al-Ishlah - Ardyansyah, Wahyudi (Zabags International Journal of Economy, 2023)
This research aims to find out the technical implementation of witnesses for wealthy customers who postpone payments at the BMT Syariah Al-Ishlah Cooperative in accordance with the fatwa of the Indonesian Ulema Majlis sharia council, find out how to deal with wealthy customers who are reluctant to pay their obligations and find out what steps are taken. what must be done if something like that happens. We can also find out what losses impact the cooperative's finances.By looking at the level of bad credit from year to year, we want to know the extent to which sharia financial institutions are implementing the fatwa of the national sharia council because the implementation of a fatwa is an instrument that is used as the basis for muamalah (transactions). Descriptive analysis is used as reference material in this research so that we can convey the results of our research by explaining it in written form taken from interviews and data. The research results show that there are sanctions in the form of infaq imposed on customers who default, and sharia financial institutions will provide free time for those who are late in paying their obligations. As well as rescheduling the records at the agreed time, the control system they implement is to approach the community to find out the reasons why they are late in payments, by visiting their homes intensively, apart from that there are also warning letters which are gradually starting. from the warning to the decision to sell the collateral, or by establishing a new contract.